Post-natal macro- and microscopic changes of the thymus of Sonali chicken in Bangladesh - Ayman, Ummay; Alam, Md Rafiqul; Das, Shonkor Kumar (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: Avian lymphatic system plays a very significant role in immunity as well as disease control. This research aimed to investigate the histomorphological changes and involution of the thymus of Sonali chicken at different post-natal stages in Bangladesh as the age-related changes of the thymus of Sonali chicken were not described before. Materials and methods: A gross and microscopic investigation was performed on the thymus of 25 healthy Sonali chickens representing different stages of post-natal life: days 1, 14, 28, 42, and 56. Experimental chickens were sacrificed by cervical subluxation, and the thymus was collected and subjected for both the gross and histological studies. The histological changes were examined with light microscopy after H&E staining. Results: The thymus was located in close association of the jugular vein, having a long chain of thymic lobes, 5–8 lobes on each side. The statistically significant age-related changes were observed (p < 0.05). All gross parameters (weight, length, width, and thickness) found to be increased up to day 42. On day 56, the growth was found to decline from the previous groups. The microscopic observations revealed the same pattern of changes such as gross parameters, i.e., continuously increased till day 42 and then declined (p < 0.05). At day 56, the involutory signs such as partial loss of interlobular septa and accumulation of adipose tissue in connective tissue septa were found. Conclusion: It is well known that in chicken, after a certain period, the thymus got involuted. In Sonali chicken of Bangladesh, the age of involution was notified at day 56/8th week of the post-natal stage, which was correlated both in macro- and microscopic observations. Adv. Vet. Anim. Res., 7(2): 324-330, June 2020